Impact of financial inclusion on firms’ growth in African nations - Hayatu, Ahmed; Matemilola, Bolaji Tunde; A. N., Bany Ariffin; Wei Ni, Soh (Human Resources Management Academic Research Society (HRMARS), 2024)
The paper examines financial inclusion's impact on firms' growth in African countries. The paper employs the two-step system generalized method of moment (GMM) to mitigate endogeneity concerns and covers 2010 to 2019 periods to exclude the impact of the covid-19 crisis on the estimated parameters of the models. The findings show that automatic teller machines, acting as a proxy for financial inclusion, positively influence the growth of firms in ten African nations. Similarly, bank branches, which also serve as a proxy for financial inclusion, positively influence firms' growth in ten African nations. The results are robust to alternative model specifications. The results suggest that investors may benefit from firms’ business expansion as banks' financial inclusion strategy attracts additional deposits to lend to firms to fund profitable investments which stimulate their growth.